Endoglucanase Activity in Lettuce Plants Colonized with the Vesicular-Arbuscular Mycorrhizal Fungus Glomus-Fasciculatum - Garcia Garrido, J.M. (1992)
Fil: Garcia Garrido, J.M.. Department of Microbiology. Estacion Experimental del Zaidin, Prof. Albareda. Granada; Spain